Epistemologies of Access: Hugh Tracey’s Organizing Principles at the International Library of African Music (ILAM) - Pooley, Nicole Madeleine (MUSICultures, 2025)
Hugh Tracey’s classification and codification strategies have laid the foundation for enhanced access to archived living heritage in the International Library of African Music (ILAM). This article considers how Tracey’s episteme in developing these organizing principles, introduced as epistemologies of access, enables stakeholders access to accurate information with fidelity to its context of origin. The ethical dimensions of enhanced access are contextualized within South Africa’s transition to a constitutional democracy. Translating catalogue entries into source languages and, in turn, translating the metadata, which is derived from those catalogue entries, into source languages and making it accessible online is suggested as an ethically responsible action and a practical measure toward enhancing access for stakeholders.